(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
Albertanus of Brescia (c. 1190s - c.1250s) is nowadays considered by international historiography as one of the key figures of the Middle Ages. Judge, politician, writer, preacher, he was the author of three moral-didactic treatises and five confraternity sermons that enjoyed great diffusion, both in their original Latin and in subsequent translations in many European languages. he’s been attributed the pedagogical and ethical project of building the medieval civis, member of the religious community and of the state as well. Through the lens of a codex of the Trivulziana Library, belonged in the late 14th century to two Milanese brothers, we’ll try to check the success of this project, deepening some aspects of the catchment area and of the transmission channels of his works. In particular, they will be taken into consideration social and political environments, persistence of Latin, women’s fruition. DOI 10.17464/9788867743261